The feasibility and effects of eye movement training for visual field loss after stroke: a mixed methods study. (May 2021) - Hazelton, Christine; Pollock, Alex; Dixon, Diane; Taylor, Anne; Davis, Bridget; Walsh, Glyn; Brady, Marian C
Introduction: Visual field loss affects around 20% of stroke survivors, reducing quality of life. Eye movement training is a promising rehabilitation method, and several different interventions are used by occupational therapists. This study aimed to explore the feasibility and effects of four eye movement training interventions for stroke survivors with visual field loss. Method: A mixed methods study – quantitative n-of-1 with qualitative interviews. The participants were 11 home-dwelling stroke survivors with visual field loss. The interventions used were MyHappyNeuron, NVT, Rainbow Readers and VISIOcoach, delivered in a randomised order. Visual search, reading speed, activities of daily living and quality of life were assessed three times before intervention use, then immediately after each intervention; these were analysed visually. A final semi-structured interview was then analysed using framework methods. Results: Evidence of effect was divergent. Quantitatively there was no measured effect, but qualitatively participants reported benefits in visual skills, daily life skills and emotions, which varied by intervention. Median training time was 3–4 hours (range 0.5–6.5) for NVT, Rainbow Readers and MyHappyNeuron, and 9.5 hours (range 2.3–16.8) for VISIOcoach. Conclusion: Eye movement training interventions were feasible for stroke survivors at home. Qualitative evidence suggests that variations in the eye movements trained and delivery modality underlie variations in perceived effect.